Electrolysis as a Universal Approach for Isolation of Diverse Chitin Scaffolds from Selected Marine Demosponges - Krzysztof Nowacki; Maciej Galiński; Andriy Fursov; Alona Voronkina; Heike Meissner; Iaroslav Petrenko; Allison L. Stelling; Hermann Ehrlich (Marine Drugs, 2022)
Three-dimensional chitinous scaffolds often used in regenerative medicine, tissue engineering, biomimetics and technology are mostly isolated from marine organisms, such as marine sponges (Porifera). In this work, we report the results of the electrochemical isolation of the ready to use chitinous matrices from three species of verongiid demosponges (Aplysina archeri, Ianthella basta and Suberea clavata) as a perfect example of possible morphological and chemical dimorphism in the case of the marine chitin sources. The electrolysis of concentrated Na2SO4 aqueous solution showed its superiority over the chemical chitin isolation method in terms of the treatment time reduction: only 5.5 h for A. archeri, 16.5 h for I. basta and 20 h for the S. clavata sample. Further investigation of the isolated scaffolds by digital microscopy and SEM showed that the electrolysis-supported isolation process obtains chitinous scaffolds with well-preserved spatial structure and it can be competitive to other alternative chitin isolation techniques that use external accelerating factors such as microwave irradiation or atmospheric plasma. Moreover, the infrared spectroscopy (ATR-FTIR) proved that with the applied electrochemical conditions, the transformation into chitosan does not take place.